REVOLUTIONIZING HEALTHCARE: THE ROLE OF ARTIFICIAL INTELLIGENCE AND BIG DATA IN PRECISION MEDICINE - Azizaxon Baxodirova; Ruxsora Isroilova; Sardor Normamatov; Ulug’bek Safarov; Polvon Otaxonov; Avazbek Koraboyev (Modern American Journals, 2025)
The integration of Artificial Intelligence (AI) and Big Data into the medical field is redefining the landscape of healthcare through the advancement of precision medicine. This article explores how these digital technologies enable more accurate diagnostics, targeted therapies, and predictive healthcare models tailored to individual patients. AI algorithms are enhancing medical imaging analysis, early disease detection, and treatment recommendations, while big data analytics are empowering large-scale epidemiological studies and real-time health monitoring. The article also examines the ethical, technical, and infrastructural challenges that accompany these innovations, particularly in under-resourced settings. By analyzing current trends and case studies, the article underscores the transformative potential of IT in delivering more personalized, efficient, and equitable healthcare.
Keywords: Artificial Intelligence, Big Data, Precision Medicine, Healthcare Technology, Predictive Analytics, Personalized Treatment, Medical Imaging, Telemedicine, Health Informatics, Data Privacy, Digital Health, Epidemiology.